Infection by Histoplasma capsulatum, Cryptococcus spp. and Paracoccidioides brasiliensis in bats collected in urban areas - da Paz, Giselle S. [UNESP]; Adorno, Brunna Mayla V. [UNESP]; Richini-Pereira, Virgínia B.; Bosco, Sandra M. G. [UNESP]; Langoni, Helio [UNESP] (Hindawi, 2018)
Epidemiological studies on endemic mycosis can be improved using molecular biology techniques to elucidate the role of bats as reservoirs and vectors of pathogenic fungi for infection of other animals and humans. The objective of this study was to explore the presence of Histoplasma capsulatum, Cryptococcus spp. and Paracoccidioides brasiliensis in insectivorous, frugivorous and nectarivorous bats collected in urban areas. We analysed 172 bats collected by the Epidemiological Surveillance Agency in 12 municipalities of the Midwest region of the state of São Paulo, Brazil. Spleen, liver, intestine and lung samples were subjected to microbiological culture and nested PCR analyses. Prevalence of H. capsulatum infection was 8.1% (14/172), with one bat found to be positive by fungal culturing, 12 positive by nested PCR and one positive by both methods. Two insectivorous bats were found positive by nested PCR for Cryptococcus spp., one in the spleen and the other in the spleen and lung. Two insectivorous bats showed natural infection by P. brasiliensis, in the spleen of one bat and the spleen and liver of the other. Our results reinforce the importance of bats as fungal dispersers in urban environments and the importance of constant epidemiologic surveillance because these synanthropic animals are in close contact with humans and animals.
Keywords: Chiroptera; fungi; nested PCR; systemic mycoses; zoonosis